Commercial bank management - Rose, Peter S. (Boston, Mass : Irwin/McGraw-Hill, 1999)
Designed to help those students who are considering a career in banking, this text provides a view of the subject from the perspective of both a bank customer and bank manager. This edition features expanded sections on asset liability management and investment banking.
Includes bibliographical references and index.
Keywords: Bank management; Financial services industry -- Management